2003
DOI: 10.1007/s00247-003-0899-4
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy in aneurysmal bone cysts in children: a review of 17 cases

Abstract: Percutaneous sclerotherapy of aneurysmal bone cysts with Ethibloc is safe and effective. It is an important alternative to surgery, especially when surgery is technically impossible or not recommended in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 25 publications
1
45
1
3
Order By: Relevance
“…Instillation of sclerosant into the lesion based on Lichtenstein's hemodynamic theory [26] was used to circumvent these limitations and possibly achieve higher healing rates. The preliminary reports regarding the use of sclerotherapy have been encouraging [1,14,16,19,22,38]. We compared the use of polidocanol as a sclerosant with intralesional excision performed with high-speed burring (extended curettage) and bone grafting to determine whether repetitive sclerotherapy is efficacious in terms of achieving primary healing rates and reducing recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instillation of sclerosant into the lesion based on Lichtenstein's hemodynamic theory [26] was used to circumvent these limitations and possibly achieve higher healing rates. The preliminary reports regarding the use of sclerotherapy have been encouraging [1,14,16,19,22,38]. We compared the use of polidocanol as a sclerosant with intralesional excision performed with high-speed burring (extended curettage) and bone grafting to determine whether repetitive sclerotherapy is efficacious in terms of achieving primary healing rates and reducing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotherapy [1,6,9,10,12,14,19,22,45] is a newer treatment modality [1] introduced in the 1990s, although the comparative safety (complications) and efficacy (recurrences) have not been as clearly established as for surgical methods. Sclerotherapy is based primarily on the premises that ABC is a vascular malformation predisposed on a hemodynamic disturbance and would heal if the vascular lesion is controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El tratamiento radioterápico se encuentra en discusión debido a que se han encontrado casos que han desarrollado osteosarcomas postradiación 4,10 . Por lo tanto es difícil justificar el uso de un agente carcinógeno potencial ante una lesión benigna cuando han sido utilizados otros métodos de tratamiento adyuvante como la embolización arterial en el tratamiento de tumores en región torácica y lumbar con resultados satisfactorios 9,12 . La embolización selectiva es eficaz en casos de difícil acceso, excepto en aquéllos que presentan fracturas patológicas o síntomas neurológicos, en los que es necesario realizar cirugía 2,11 .…”
Section: Discussionunclassified
“…Adjuvant radiation has been associated with malignant transformation and is therefore not recommended; however, cases have progressed to malignancy without prior radiation [50] . Sclerotherapy is an alternative with relative success for aneurysmal bone cysts not amenable to surgical treatment, although we cannot find a case of sclerotherapy for an orbital lesion [51,52] . Recently, Pelle et al [53] have demonstrated strong RANK ligand expression in stromal cells in vivo and tumor shrinkage in a 5-year-old boy with a large sacral aneurysmal bone cyst treated with denosumab [54] .…”
Section: Benign Reactive Bone Lesions Of the Orbitmentioning
confidence: 99%